SOCIODRAMA-BASED GROUP GUIDANCE INTEGRATING BHUPPA’ BHABBU’ GHURU RATO VALUES TO DEVELOP RESPECTFUL ATTITUDES IN HIGH SCHOOL STUDENT - Erfan Nawawi; Muslihati Muslihati; Diniy Hidayatur Rahman (Jurnal Konseling Pendidikan Islam, 2026)
The moral crisis among students, reflected in the increasing cases of bullying, disrespectful behavior, and declining respect toward teachers and parents, highlights the urgency of character education grounded in local cultural wisdom. This study aims to conduct a Systematic Literature Review (SLR) to identify, analyze, and synthesize previous research on group guidance using sociodrama techniques, the cultural values of Bhuppa’ Bhabbu’ Ghuru Rato (BBGR), and their integration in fostering respect among senior high school students. Data were collected from Scopus and Google Scholar databases with a publication range between 2020 and 2025. Out of 268 initial studies, 13 articles met the inclusion criteria and were analyzed. The findings indicate that sociodrama is effective in reducing discriminatory attitudes, enhancing empathy, interpersonal communication, and students’ politeness, while BBGR values emphasize a hierarchical respect toward parents, teachers, and leaders as moral foundations for character education. The integration of these elements results in a conceptual model of group guidance that is contextual, culturally responsive, and supportive of Indonesia’s national character education policy. The main contribution of this study lies in constructing an integrative counseling model that combines modern counseling approaches with local cultural wisdom. Future studies are recommended to empirically test this model through experimental or qualitative designs in schools to evaluate its effectiveness, acceptability, and sustainability.